Local Wisdom-Based Pictorial Teaching Materials: A Strategy for Boosting Ecoliteracy in Elementary School Students - Yonanda, Devi Afriyuni; Haryanti, Yuyun Dwi; Kurino, Yeni Dwi; Rosidah, Ani; Sofiasyari, Irma (Universitas Muhammadiyah Surakarta, 2023)
The pervasive influence of various advertisements across multiple media platforms, promoting instant and packaged food and beverages, has contributed to the unhealthy lifestyle habits of learners. Examples include the consumption of foods or beverages detrimental to health. Non-environmentally friendly materials can also have a negative impact on the environment. Consequently, there is a need for individuals to understand and recognise the importance of consuming healthy and environmentally friendly local food. This research examined the validity of pictorial teaching materials based on the local wisdom of Indramayu, aimed at enhancing learners' eco-literacy skills. The study was conducted among fourth-grade students at Public Primary School A and B in Indramayu. The research model applied was Borg & Gall's model. The researchers validated the product based on content, language, and graphic reliability. The validation process involved three experts and two practitioners. The data validity test incorporated interviews, observations, and documentation. The results demonstrated that the content reliability was 87.50%, language validity was 89.16%, and graphic validity was 91.66%. These results indicated a category of high validity. The findings suggested that the pictorial teaching material, grounded in Indramayu local wisdom, was beneficial for further learning. Future researchers could extend this research by developing other forms of teaching materials